Do Māori Rights Racially Discriminate Against Non Māori? - Charters, Claire (Victoria University of Wellington Law Review, 2009)
Claire Charters argues that the claim that Māori rights discriminate against non-Māori needs to be tested to a greater extent than it has been in both political and academic circles to date, not least because of its importance to the type of nation New Zealand is and seeks to be. She illustrates that from a contextual, comparative and theoretical standpoint Māori rights do not discriminate against non-Māori and to suggest that they do so will only increase Māori’s detachment from the New Zealand polity.